Care of the organ transplant receiver: Review: Organ recipient preparation - Bektas, Neslihan (Journal of Surgery and Medicine, 2022)
Organ transplantation is the process of replacing damaged/inoperative organs with healthy ones. Many parameters are considered in the decision-making process for this procedure. At first, compatibility parameters of the recipient individual and the donor should be evaluated. All laboratory values and tissue compatibility tests should be compared. The organ transplant coordinator shares the patient’s compliance information with the team. The recipient patient is informed of the match, and the process begins. Preparing the recipient for transplantation is as difficult as finding the appropriate organ. During the first stages, the individual is evaluated and meets with the entire transplant team. Everyone on the transplant team explains their roles and responsibilities. The patient can ask questions. Information is given about complications and negative care processes encountered after transplantation. Patients most often experience differences of opinion in religious and cultural dimensions. On the one hand, he/she wants to live; on the other hand, he/she thinks transplantation is a “sin”. These confusing thoughts can increase and be replaced by psychosocial issues. The transplant nurse initiates the patient’s rehabilitation process. This process is based on an immunosuppressive treatment plan to strengthen the patient’s immunity before transplantation. The transplantation plan provides guidance on transplant day, donor patient preparation, and organ safety. This review serves as a guide for recipient individual. This review study consists of specific sub-titles related to the subject.